PENERAPAN METODE THINK TALK WRITE DALAM PEMBELAJARAN MENULIS TEKS CERPEN PADA SISWA MENENGAH ATAS - Indri Uliana; Hulwa Firsty Dananjaya; Restu Bias Primandhika (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
Researchers find problems in learning short story texts students find it difficult to express ideas and imagination. Researchers use the think talk write method to motivate students and develop ideas and imagination in writing short story texts. The Think Talk Write method is a way of teaching students to develop skills with their own business. This study aims to determine the differences in the ability and implementation of student learning applied to the treatment of Discovery Learning models in the control class and students who applied the think talk write treatment method in the experimental class. In this study the method used is the Quasi Experimental Design used is the pretest-postest Control Group Design. The objects that were sampled in this study were 30th grade XI-A students, and 30th grade XI-B students. Based on the results of the study, it can be concluded that the think talk write method is better than the Discovery Learning model. When students are treated with the think talk write method the value obtained is very good, can be seen from the posttest results the average student gets a score of 76.70, compared to when students are treated (treatment) using the average Discovery Learning model the students only get a score of 56.50.